Pancasila as a Source of Law in Enforcing Corruption in Indonesia - Nugroho, Andre Setyo (Faculty of Law, Universitas Negeri Semarang, 2023)
Indonesia is currently in a state of emergency in law enforcement, especially in cases of corruption. Law enforcement in Indonesia is still quite alarming because the law in Indonesia still views the public and officials, this view is certainly not equal and not in accordance with the values ​​contained in Pancasila. With the inequality of legal equality of corruption, there are many problems ranging from health to the economy. Corruption is an act that is very detrimental in various sectors, especially in its enforcement that is not in accordance with the values ​​of Pancasila which causes enforcement in Indonesia to be very sad. In the discussion of this journal, it focuses more on the values ​​of Pancasila so that law enforcement in Indonesia returns to normal or enforcement in Indonesia can be said to be equivalent which contains the values ​​of Pancasila in it. In taking the material in this journal, we use the library study method which will add insight into how to take the attitude of Pancasila values ​​in law enforcement corruption.